9 Strategi Pembiayaan Dan Analisis Keuangan Perusahaan Maskapai Di Bursa Efek Indonesia - Ristiani (Sekolah Tinggi Teknologi Kedirgantaraan, 2019)
This research used quantitative descriptive methods to study the literature and to analyze secondary data in the form of financial performance summary of the three companies collected through the Indonesia Stock Exchange website. Data was analyzed by using liquidity ratio, activity ratio, Debt to Total Assets (DTA), and profitability ratio. The result shows that the three companies use aggressive strategies in financing their operational activities, PT Garuda Indonesia Tbk has the best ability to pay its short-term liabilities, PT AirAsia Indonesia Tbk is the fastest in turning its business receivables into cash but its financial risk is greater than the other two airline companies because more than 100% of funding comes from debt. PT AirAsia Indonesia Tbk and PT Garuda Indonesia Tbk can generate a gross profit of 1 rupiah per 1 rupiah of sale, but are declared to suffer losses because Operating Profit Margin (OPM) and Net Profit Margin (NPM) are both negative; the three companies have not been able to generate profits from the use of their assets; also PT Garuda Indonesia Tbk and PT Indonesia Transport & Infrastructure Tbk have negative Return on Equity (ROE) value due to loss (negative net income), even though the equity is positive. This comparison of financial analysis can not directly reveal the financial strength and weakness of each company because more information is needed, especially regarding the terms of debt and receivables in the industry.